# Calculator search results

Formula
Solve the equation
Graph
$y = 4 x - \left ( 3 + 5 x \right )$
$y = 2 \left ( x - 1 \right ) + 1$
$x$Intercept
$\left ( - 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - 3 \right )$
$x$Intercept
$\left ( \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 1 \right )$
$4x- \left( 3+5x \right) = 2 \left( x-1 \right) +1$
$x = - \dfrac { 2 } { 3 }$
 Solve a solution to $x$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \right ) = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 1 + 3$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = - 1 + 3$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Organize the expression 
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
 그래프 보기 
Graph
Solution search results